Analysis of the Application of Artificial Intelligence Technology in the Field of International Trade - Li, Penghua (Transactions on Economics, Business and Management Research, 2024)
With the rapid development of artificial intelligence technology, its application in the field of international trade has gradually become a hot spot for research. The purpose of this paper is to analyze in depth the prospects for the application of AI technology in international trade and to explore the opportunities it brings to international trade as well as the challenges it faces. Firstly, this paper reviews the development status of international trade and the latest progress in artificial intelligence technology to provide a background for the study. Subsequently, through the construction of a theoretical framework and the application of an integrated research methodology, the specific applications of AI in international trade are analyzed in detail, including smart contracts, data analytics, automated processes, and its role in logistics and supply chain management. Further, the paper discusses the positive impacts of AI technology applications, such as improved transaction efficiency, cost reduction, and enhanced market forecasting capabilities, while also pointing out the accompanying challenges, such as technological barriers, adaptation of laws and regulations, talent requirements, and data security. Through case studies, the paper demonstrates the effects and lessons learned from the application of AI technology in actual international trade. Finally, the paper summarizes the research findings, makes recommendations for future applications of AI technology in international trade, and explores directions for subsequent research. This study aims to provide some insights into the application of AI technology in the field of international trade as well as usable references for future development.